Thyroid hormone level is associated with the frequency and severity of acute transverse myelitis. Issue 5 (22nd March 2017) - Weng, Yiyun; Lin, Huiyue; Ye, Xiaoxian; Xie, Dewei; Chen, Zhibo; Zheng, Juzeng; Su, Zhongqian; Xie, Hongli; Zhang, Xu; Li, Xiang
Abstract : Acute transverse myelitis (ATM) is a progressive and autoimmune disease with inflammatory cell infiltrates into the spinal cord, and thyroid hormone (TH) level is associated with the oxidative and antioxidant status. Variations in oxidative stress and antioxidant levels are related to the pathogenesis of autoimmune and inflammatory diseases. Our study aimed to investigate the possible correlation between ATM and TH levels of thyroid-stimulating hormone (TSH), free thyroxine (FT4 ), free triiodothyronine (FT3 ), and FT4 /FT3 . We measured serum concentrations of TSH, FT4, and FT3 in 205 individuals, including 42 ATM patients, 49 multiple sclerosis patients, and 114 healthy controls. Our findings show that ATM patients had lower levels of TSH and FT3 and higher levels of FT4 and FT4 /FT3 compared with healthy controls, whether male or female. Moreover, levels of TSH and FT3 in patients with ATM were inversely correlated with disease severity measured by the Expanded Disability Status Scale. Variations in TH level may represent the oxidative status and are surrogate biomarkers of the incidence and severity of ATM.